Manual de produção de mídia digital em formato podcast como estratégia de fortalecimento da comunicação interna da Rede EBSERH - Passos, Paula Morena Braga (2021)
INTRODUCTION: The Brazilian Hospital Services Company (Ebserh) is the largest hospital network in Brazil with 100% service offered by SUS. The state-owned company is linked to the Ministry of Education and offers a reference medical-hospital service, through teaching and learning to train health professionals. The institution has more than 60.000 employees and, as a result, it is essential that the communication area is attentive to the opening and unblocking of information channels to engage people and match the requirements of employment and employer. Among the main internal communication problems of the company is the difficulty in reaching all employees due to the diversity in the scope of work assignments and work processes, as well as because access to digital information is difficult in the work environment, considering that the employee of health care does not have an individual workstation with a computer and the work dynamic does not allow continuous access to information in the digital communication channels currently used by the company. In addition, the information in the models used by the company often fall into the routine, become monotonous, unattractive and end up being trivialized. Thus, important news, facts and announcements end up being lost because they do not reach employees in a timely manner. OBJECTIVE: The purpose of this work is to encourage, through the Podcast Preparation Manual for the Ebserh Network, the use of digital media in podcast format as a strategy to strengthen the institution's internal communication, as it is a mobile digital media that enables the consumption of news dynamically, by transmitting information via the internet, by cell phone or computer, online or offline, giving the listener the freedom to choose the best moment: when to listen, where to listen and how to listen. METHODOLOGY: The research was carried out in 6 (six) stages of development - bibliographic survey, theoretical framework study on the production of podcasts, identification of the main communication problems in the Ebserh Network, mapping of the podcast production process, preparation of the Manual of Podcast production and pilot podcast production. RESULTS: Based on the guidelines to obtain no manual, it was possible to produce and publish podcasts confirming the applicability of the method. The podcast was deployed at Ebserh's central administration. CONCLUSION: In fact, there is a technical simplicity to produce and distribute a podcast, in addition to being low cost, eliminating the need for large teams and with sound quality. The media production process map and the manual can be replicated or redesigned and known by the hospitals' social communication areas, according to local realities and needs.